Reliability evaluation of electric power systems considering the voltage stability - Toh, Alvin Jian Feng. (2011)
With the growth of technology and automation, the demand for power is ever increasing. As the focus of today’s technology shifts towards the sophisticated frontier, the demand for good quality power from the power stations is even more imperative. In the instance of a post-contingency situation, power quality will suffer in various aspects such as voltage and frequency variations. These discrepancies will cause delicate electronics used today, as compared to their electromechanical predecessors, to breakdown. Therefore it is of utmost importance that a power system is able to handle all of the possible scenarios that might happen and still be able to function properly. Reliability evaluation has always been a major tool for system planners to evaluate their power system. These indices will inform the system planners the severity of post-contingency situations and hence prompt the planners to install proper corrective measures. Inadequate attention paid to these indices will cause huge amount of economic losses in the event of plant failure(s). However much of the studies and researches into this field did not investigate the effect on reliability evaluation with respect to reactive power inadequacy. This paper will attempt to separate and evaluate a set of reliability index (ELCQ, EQCQ, EENSQ, EVNSQ & EVarS) from the conventional reliability indices. A MatLab program was coded to calculate all the relevant reliability indices in post contingency situations. Analysis shall then be carried out to find out the effects of voltage set point, reactive power compensation devices and load curtailment on voltage stability.